Gluten-Free Labeling Is Misused Frequently in Foods Marketed in Northwestern Mexico - Calderón de la Barca, Ana M.; Luna-Alcocer, Valeria; Valenzuela-Miranda, José R.; Mejía-León, Maria E. (Frontiers in Nutrition, 2021)
Background: Celiac disease (CD) patients need a gluten-free (GF) diet, including industrialized products containing ≤20 mg gluten/kg. Its market status is almost unknown in Mexico. Therefore, we classified, studied costs, and analyzed gluten content of the GF-labeled products available in the northwest Mexican market. Methods: We looked for GF foods in 3 different supermarkets of each chain and food shop in Mexicali, B.C., and Hermosillo, Sonora, and corroborated costs, quantity, origin and GF certification on internet sites. We analyzed gluten by the sandwich R5 enzyme-linked immunosorbent assay (ELISA), and immune-detected gluten proteins with CD patients’ sera. Results: There were >263 different GF-labeled foodstuffs, 55% of them made in Mexico, principally flours, sausages, bread and bakery, milk-type products and tortillas, while pasta products, snacks and breakfast cereals were mainly imported. The cost ratio of GF to conventional mean was 3.5, ranging from 1 to 13, except to 20 for some products. The more common GF-labeled foods were flours and pasta products (34), cookies and snacks (32), breakfast cereals, sausages and milk-type products (18-20). While 36% of the products presented a certification, 17.4% of the analyzed samples contained >20 mg gluten/kg, mainly the non-certified ones and made in Mexico. IgA from CD patients reacted in blots to gluten proteins from the GF-labeled products. Conclusion: The accessibility of GF products in the Mexican northwest market is wide, although usually expensive, and some could be risky for CD patients due to their content of gluten, which is recognized by their immune system.